Model Integrasi Ekonomi Maritim Dan Pariwisata Di Daerah Guna Peningkatan Ekonomi Indonesia Timur - I Nyoman Sudapet; Agus Sukoco; M. Ikhsan Setiawan (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
Maritime economic growth and increasing tourism economy Marine Highway program are supported. BPS data (2016) states the number of foreign tourists visiting Indonesia during January-April 2016 reached 3.52 million visits, up 7.51 percent compared with the number of foreign tourists in the same period in 2015, which totaled 3.27 million visits. Additionally related maritime economy, the data agency said the number of goods transported in domestic shipping April 2016 reached 20.8 million tons, up 1.98 percent compared to the previous month and rose 16.50 percent over the same month in 2015. Growth in Indonesia east must be used optimally by the Government to develop a model of economic integration Maritime and Tourism. This study aims at modeling, mapping and economic feasibility of the Maritime Economic Integration and Tourism in the area in order to improve the economy of Eastern Indonesia, with the manufacture of a Geographic Information System that supports the economic development. The study was conducted in the years 2017-2018, Year The first is modeling, mapping and analysis of the feasibility of Economic Integration Model Maritime and tourism in the area in order to improve the economy of eastern Indonesia. result in Research published in the Seminar / International Proceedings, International Journal Scopus indexed and submitted to the Ministry of Justice and Human Rights to obtain IPR Copyright on the application of Geographic Information Systems Integration development of Maritime Economy and Tourism in Eastern Indonesia